Effects of forestry on the structure, diversity and dynamics of mixed stands in the Sierra Juárez, Oaxaca - Ramírez Santiago, Rosario; Ángeles Pérez, Gregorio; Hernández de La Rosa, Patricia; Cetina Alcalá, Víctor Manuel; Plascencia Escalante, Ofelia; Clark-Tapia, Ricardo (Instituto de Ecología, A.C., 2019)
Silvicultural practices tend to simplify the composition and structural complexity of the forest. The purpose of this study was to assess the changes in forest structure, tree diversity and demographic dynamics of mixed-wood stands harvested by group selection (GS) and seed tree (ST) regeneration methods in the Sierra Juárez of Oaxaca, Mexico. In addition, an unharvested forest was included in the evaluation as a reference site (RF). Data for this study (base area, diameter, height, survival and recruitment) come from 29 permanent sampling plots of 1000 m2 established in the 2007-2012 period. The results revealed that the GS and ST demonstrated rapid growth, despite the high density of the operating areas. In both sites, a similar silvicultural criterion was applied, and this may have been the reason these sites showed no differences in forest structure, annual timber volume increment and species diversity or species richness. However, the GS forest showed features similar to ST, on a wider tree diameter distribution and a higher diversity index for tree species than the RF site. The results generated contribute to the understanding of the ecological processes of the pine-oak ecosystems and to implement the best silvicultural system. Development of intensive forest management that incorporates characteristics of mature forests are recommended as the best practice in terms of forest productivity and ecosystem conservation, in the Sierra Juárez of Oaxaca.